Εmbiricos Lecteur de Proust - Bouchard, Jacques (Études helléniques / Hellenic Studies, 1995)
The personal library of Andreas Embiricos (1901-1975) includes nine volumes of the complete words of Marcel Proust, which were acquired beginning May 17, 1926. Several volumes contain marginal notes and passages underlined by Embiricos. These annotations promise to be of capital importance in the further study of modern Greece’s first surrealist poet and psychoanalyst.